Effect of application time of 38% SDF on ECC (RCT) - Dr Iliana Gehui Yan; Dr Faith Miaomiao Zheng; Prof. Chun Hung Chu; Prof. Edward Chin Man Lo (Elsevier, 2023)
Aim or Purpose: To study the caries lesion activity response to topical 38% silver diamine fluoride (SDF) therapy with increasing treatment application time. Materials and Methods: The design was a stratified-randomised, double-blind, active-controlled, parallel-group clinical trial with nine treatment arms. The trial recruited 747 3- to 5-year-old kindergarten children with caries, who received 38% SDF to treat each carious lesion surface. The children were stratified by caries status, randomised by blocks, and allocated to nine groups of SDF application times: 3, 5, 10, 15, 30, 45, 60, 120, and 180 s. The outcome measure is caries lesion activity (active/arrest) at the tooth-surface level at 6 months post-initial treatment. The generalized estimating equations (GEE) approach used to determine the relationship between the exposure to SDF (the SDF application time) and the response (proportion of lesions arrested) and adjust the effect of correlation since multiple lesions could be included in a child. Results: A total of 747 children with 4,018 decayed tooth surfaces received SDF application at baseline, and 709 (94.9%) children with 3,541 surfaces (88.1%) were evaluated at the 6-mo examination. The caries arrest rates were 76.8%, 77.2%, 81.6%, 82.8%, 83.8%, 85.6%, 86.0%, 85.8% and 87.5% for nine groups of SDF application times, respectively (P < 0.001). Caries treated with 38% SDF after 5s application time had 80% chance of becoming arrested (P < 0.001). Conclusions: SDF at a concentration of 38% is more effective with longer SDF application time in arresting active caries in primary teeth. The caries arrest rates were achieved 80% after 5 s.